Strengthening inclusive entrepreneurship: Excel-based COGS literacy for special needs educators - Rahma Nur Praptiwi; Tika Dwi Ariyanti; Genesa Vernanda; Innas Rovino Katuruni; Sri Isti Untari; Anita Rahmawati; Kristin Lukitaningrum; Maria Nino Istia; M. Jamal Al Bakri (Community Empowerment, 2026)
Limited numerical literacy and the lack of systematic learning media are primary obstacles to teaching entrepreneurship to Individuals with Special Needs (IBK). This community service program aims to enhance the capacity of educators at Yayasan Sanur Akademi Inspirasi in delivering visual and measurable Cost of Goods Sold (COGS) calculation materials. The implementation methodology utilized a participatory approach through intensive training, Microsoft Excel-based technical mentoring, and the development of adaptive modules. Results demonstrated a significant improvement in teachers' technical skills in constructing applicable COGS simulations for students. Program outputs, including automated Excel templates, learning modules, and video tutorials, have been integrated into the foundation's entrepreneurship curriculum, ensuring program sustainability. This initiative proves that simple technology support, visually adapted, is effective in overcoming financial literacy barriers within inclusive education ecosystems.